Analyzing Platform Merdeka Mengajar utilization in high school teachers in Jakarta - Elsa Kurnia Hudiana; Rusman Rusman (Inovasi Kurikulum, 2025)
This study analyzes the utilization of the Platform Merdeka Mengajar by 5.046 teachers across 117 public high schools in Jakarta, aiming to evaluate the extent to which the platform is used by teachers in supporting the implementation of the Kurikulum Merdeka. The central research question is: To what extent do public high school teachers in Jakarta utilize the Platform Merdeka Mengajar to support the implementation of the Kurikulum Merdeka? Using a quantitative descriptive method, secondary data from the platform's dashboard were analyzed, focusing on three metric levels that measure activities such as independent training, teaching tools, assessments, and validated teacher actions. The findings reveal that independent training videos and teaching tools are the most frequently used features, reflecting their accessibility and relevance to teachers' professional needs. However, features such as webinars and validated actual actions show lower levels of participation, indicating a need for improvement in utilizing these features. This study concludes that the Platform Merdeka Mengajar holds great potential to support teacher professional development and the implementation of the Kurikulum Merdeka. However, further efforts are needed to enhance the use of underutilized features and adjust content to meet teachers' needs better.   Abstrak Penelitian ini menganalisis pemanfaatan Platform Merdeka Mengajar oleh 5.046 guru di 117 SMA negeri di Jakarta, dengan tujuan untuk mengevaluasi sejauh mana platform tersebut digunakan oleh guru dalam mendukung penerapan Kurikulum Merdeka. Pertanyaan utama penelitian ini adalah: Sejauh mana pemanfaatan Platform Merdeka Mengajar oleh guru SMA Negeri di Jakarta dalam mendukung penerapan Kurikulum Merdeka? Menggunakan metode deskriptif kuantitatif, data sekunder dari dashboard platform dianalisis, dengan fokus pada tiga level metrik yang mengukur aktivitas seperti pelatihan mandiri, alat pembelajaran, asesmen, dan tindakan nyata yang tervalidasi oleh guru. Hasil penelitian menunjukkan bahwa fitur video pelatihan mandiri dan alat pembelajaran merupakan fitur yang paling banyak digunakan, mencerminkan aksesibilitas dan relevansinya dengan kebutuhan profesional guru. Namun, fitur seperti webinar dan tindakan nyata yang tervalidasi menunjukkan tingkat partisipasi yang lebih rendah, yang mengindikasikan perlunya peningkatan dalam pemanfaatan fitur-fitur tersebut. Penelitian ini menyimpulkan bahwa Platform Merdeka Mengajar memiliki potensi besar dalam mendukung pengembangan profesional guru dan penerapan Kurikulum Merdeka, tetapi perlu upaya lebih untuk meningkatkan pemanfaatan fitur yang kurang digunakan dan menyesuaikan konten agar lebih sesuai dengan kebutuhan guru. Kata Kunci: impelementasi kurikulum; guru sekolah menengah atas; Kurikulum Merdeka; platform merdeka mengajar; PMM